A New Approach to Local Resource Sharing Systems: Document Supply Tracking System (KİTS) Modal Proposal - Kaya, Mert; Yöndem, Nilay Yalkan (ADA University Library, 2024)
Anatolian University Libraries Consortium (ANKOS) was established in 1999 to enhance the support of libraries to education and research by realizing the highest level of access of academic libraries in Türkiye to the global information network (ANKOS, 2024). Under the consortium’s umbrella, the "Collaboration Research Group" was formed in 2006 for resource sharing and this group implemented Document Supply Tracking System (KİTS) project. KİTS is an online platform aimed at tracking resource sharing activities carried out in university libraries and information centers. This system, which is completely free and online, is used by ANKOS member higher education institutions (KİTS, 2006)
Keywords: Anatolian University Libraries Consortium (ANKOS); Collaboration Research Group; Document Supply Tracking System (KİTS); Resource sharing; Document Supply; Academic libraries